2019
DOI: 10.3390/app9194128
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Real-Time R and QRS Detection Method Using a Pair of Derivative Filters and Max Filter for Portable ECG Device

Abstract: Recently, with the active development of wearable electrocardiogram (ECG) devices such as smart-bands or portable ECG devices, efficient ECG signal processing technology that can be applied in real-time has been actively studied. However, a wearable ECG device is exposed to various noise situations, thereby reducing the reliability of the detected R point or QRS interval. In addition, as early warning techniques in healthcare systems have been studied, real-time ECG signal processing techniques have become ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…However, the resulting signal preserves the ECG morphology. Hence, in this type of studied data, we found that the P wave was inverted (negative) [32] and this is due to the diagnostic status of the patient from which the data are drawn.…”
Section: Ecg De-noising Based the Comparison The Morphologies Of Deferent Configurationsmentioning
confidence: 63%
“…However, the resulting signal preserves the ECG morphology. Hence, in this type of studied data, we found that the P wave was inverted (negative) [32] and this is due to the diagnostic status of the patient from which the data are drawn.…”
Section: Ecg De-noising Based the Comparison The Morphologies Of Deferent Configurationsmentioning
confidence: 63%
“…However, other points like P and T waves have greater influence in a generic cardiac health analysis scenario. Similarly, the abnormality in R and Q, R, and S points are identified by others in [24] with sensitivity = 99.8%. Nonetheless, the contamination of Q and S points due to noise is not considered.…”
Section: Related Workmentioning
confidence: 84%
“…VPB is the initial manifestation of aconitine-induced arrhythmia model rats, and the ECG of VPB is characterized by premature and bizarrely shaped QRS complexes that appear wide on the ECG, these complexes are not preceded by a P wave, and a T wave is usually oriented in a direction opposite the major deflection of the QRS ( Casas et al, 2018 ; Bae and Kwon, 2019 ). VPB incubation period refers to the time after the administration of aconitine to the first occurrence of VPB ( Qiu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%